Nurturing babies : nurturing childhoods for all our tomorrows - Peckham, Kathryn (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Nurturing Babies explores the key processes behind how a child's mind and body develops in their first year, underpinned by the latest research in the fields of child development, psychology, health and well-being. It shows how the choices practitioners and parents make every day can have a deep impact on children's experiences and the practices that can be embedded straight away to support their ongoing development and give them the best opportunities for future success. The book follows a holistic approach through the Nurturing Childhoods Pedagogical Framework, learning to understand children's evolving capabilities through their engagement in core behaviours and using these to unlock their full potential. Chapters cover: - The importance of sleep and daily routines - Playing and communicating with babies - Physical activity and healthy eating - Early brain development - Understanding babies' emotions and behaviours - The importance of emotional security on a child's well-being - Supporting infants to explore and do new things Part of the Nurturing Childhoods series, this exciting book provides practitioners and parents with the knowledge and understanding they need to nurture the very youngest children, building their self-esteem, happiness and well-being as they become enthusiastic lifelong learners"--
Good practices from the start -- Connecting with Babies; Communication, Movement and Play -- Striking the right balance -- Time for rest -- Understanding Babies Responses -- Nurturing Babies Developing Behaviours -- Helping children feel competent, confident and worthy -- Empowering resilient children -- Supporting Children's Learning -- Nurturing Lifelong Learning with babies -- Section 2 Introduction -- The Nurturing Childhoods Pedagogical Framework -- Nurturing Babies to do things for themselves -- Nurturing Babies to do new things -- Nurturing Babies to be brave -- Nurturing Babies to have good ideas -- Nurturing Babies to have a go -- Nurturing Babies to have fun -- Nurturing Babies to think.
Keywords: Infants -- Development; Infant psychology; EDUCATION / Preschool & Kindergarten; EDUCATION / Elementary; EDUCATION / Professional Development